2019
DOI: 10.1111/infi.12344
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear exchange‐rate pass‐through in emerging markets

Abstract: This paper documents nonlinearities and asymmetries in the transmission of exchange rate fluctuations to prices in a panel of 27 emerging markets for the period 1990–2013. Using local projection techniques, we find evidence of asymmetry in the extent of exchange‐rate pass‐through during episodes of appreciation relative to episodes of depreciation. We then test for the presence of a threshold that can lead to nonlinearities when the exchange rate experiences a large depreciation. The findings suggest that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 67 publications
1
22
1
Order By: Relevance
“…Various studies emphasize trade openness and the composition of imported goods (Campa and Goldberg, 2005;Campa and Goldberg, 2010), central bank credibility (Taylor, 2000;Gagnon and Ihrig, 2004;Choudhri and Hakura, 2006;Mishkin and Schmidt-Hebbel, 2007;Coulibaly and Kempf, 2010;Caselli and Roitman, 2016;Carriere-Swallow, Gruss, Magud, and Valencia, 2017), the degree of competition in product markets (Devereux, Tomlin, and Dong, 2015;Amiti, Itskhoki, and Konings, 2016), in ‡ation volatility (Ca'Zorzi, Hahn, and Sánchez, 2007;Forbes, Hjortsoe, and Nenova, 2017), and exchange rate volatility (Campa and Goldberg, 2005). Other studies focus on microeconomic aspects of price-setting: nominal rigidities (Devereux and Yetman, 2002;Corsetti, Dedola, and Leduc, 2008), the role of foreign-currency pricing, especially in invoicing (Gopinath, Itskhoki, and Rigobon, 2010;Gopinath, 2015;Devereux, Tomlin, and Dong, 2015), the dispersion of price changes (Berger and Vavra, 2015), and the frequency of price adjustments .…”
Section: What Are the Key Country Characteristics A¤ecting Pass-throughs?mentioning
confidence: 99%
“…Various studies emphasize trade openness and the composition of imported goods (Campa and Goldberg, 2005;Campa and Goldberg, 2010), central bank credibility (Taylor, 2000;Gagnon and Ihrig, 2004;Choudhri and Hakura, 2006;Mishkin and Schmidt-Hebbel, 2007;Coulibaly and Kempf, 2010;Caselli and Roitman, 2016;Carriere-Swallow, Gruss, Magud, and Valencia, 2017), the degree of competition in product markets (Devereux, Tomlin, and Dong, 2015;Amiti, Itskhoki, and Konings, 2016), in ‡ation volatility (Ca'Zorzi, Hahn, and Sánchez, 2007;Forbes, Hjortsoe, and Nenova, 2017), and exchange rate volatility (Campa and Goldberg, 2005). Other studies focus on microeconomic aspects of price-setting: nominal rigidities (Devereux and Yetman, 2002;Corsetti, Dedola, and Leduc, 2008), the role of foreign-currency pricing, especially in invoicing (Gopinath, Itskhoki, and Rigobon, 2010;Gopinath, 2015;Devereux, Tomlin, and Dong, 2015), the dispersion of price changes (Berger and Vavra, 2015), and the frequency of price adjustments .…”
Section: What Are the Key Country Characteristics A¤ecting Pass-throughs?mentioning
confidence: 99%
“…ere have been numerous works in the literature that try to establish the relationship between inflation and exchange rate. Some of these works are [11,12]. In [11,12], the authors analysed the relationship between inflation and exchange rate for some emerging markets, whereas Arslaner et al [1] analysed a similar relationship using data from Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these works are [11,12]. In [11,12], the authors analysed the relationship between inflation and exchange rate for some emerging markets, whereas Arslaner et al [1] analysed a similar relationship using data from Turkey. Choudhri and Hakura [2] also analysed the relationship between inflation and exchange rate using data from several industrialised and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…This is the likelihood-ratio test (LR) available in the open-source package tsDyn. 12 The test is a multivariate extension of the test proposed by Lo and Zivot (2001) to the Hansen (1999) linearity test. In particular, it compares the determinant of the estimated variance-covariance matrix of each model as shown below:…”
Section: Nonlinearity Testmentioning
confidence: 99%
“…Given the magnitudes of these changes, the question of potential nonlinearities in the transfer of exchange rate movements to inflation gained relevance. The literature has suggested that episodes of extreme exchange rate depreciation can lead to different degrees of pass-through, such as the findings presented in Caselli and Roitman (2016) and Bussiere (2013). For this reason, this paper aims to investigate whether the exchange rate pass-through (ERPT) to consumer prices follows a nonlinear behavior in Mexico.…”
Section: Introductionmentioning
confidence: 95%